Economic value of protected areas via visitor mental health - Ralf Buckley (Nature Portfolio, 2019)
Parks have a previously unquantified economic value attributable to mental health, a health services value. Here, the authors proposed three methods to estimate this, and applied one of these methods to show that this value is at least US$6 trillion per annum worldwide.